Rulings of mummification in Islamic Law - Muhammad Husni, Ahmad (Medwell Journal, 2013)
The right to life is sacred in the eyes of the Shariah. Allah (swt) created man, dignified him and preferred him on my creatures with reason, knowledge, expression, and nice and noble shape when he was in the womb and in all stages until he was created by Allah, the best of creators. The Shariah has forbidden unjust attack on someone even a dead body it is not allowed to tamper with it. The problem lies in some questions about mummification and differences of opinions and fatwa related to that in terms of medical perspective or for other purposes. Thus, this study aims to highlight ruling of mummification in the Shariah which aims at protection of life, and to highlight the views of contemporary jurists regarding the issue and also the opinions of medical doctors. The study followed the induction and historical approach to study the opinions of jurists and scholars to detect the ruling with the changes through time. The study concluded that mummification of human corpse is prohibited because it is a violation of Allah’s way of burial even if it is for the sake of study or research; and mummification of animals and birds is prohibited as well if it is for the purpose of adornment and boasting because it is a waste of money.